Rapid Information from Household High-Frequency Survey : Summary of Results from Round 4 - World Bank (World Bank, Washington, DC, 2020)
The brief presents the main findings from the fourth of eight rounds of a nationally representative survey of 1,500 randomly selected households in all states/regions of Myanmar. The survey was undertaken by conducting a 20-minute phone call with respondents from 7th to 29th October 2020.